1987
DOI: 10.1056/nejm198708063170602
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cryptococcal Meningitis with Combination Amphotericin B and Flucytosine for Four as Compared with Six Weeks

Abstract: One hundred ninety-four patients with cryptococcal meningitis were enrolled in a multicenter, prospective, randomized clinical trial to compare the efficacy and toxicity of four as compared with six weeks of combination amphotericin B and flucytosine therapy. Among 91 patients who met preestablished criteria for randomization, cure or improvement was noted in 75 percent of those treated for four weeks and in 85 percent of those treated for six weeks. The estimated relapse rate for the four-week regimen was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
181
2
7

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(196 citation statements)
references
References 15 publications
6
181
2
7
Order By: Relevance
“…A diminuição do nível de consciência tem sido descrita como preditora de letalidade em diversas encefalites infecciosas 10,13,18,19 . Acreditamos que este dado traduza maior agressão encefálica que muitas vezes está associada a hipertensão intracraniana, vasculite e alterações eletrolíticas.…”
Section: Variáveisunclassified
“…A diminuição do nível de consciência tem sido descrita como preditora de letalidade em diversas encefalites infecciosas 10,13,18,19 . Acreditamos que este dado traduza maior agressão encefálica que muitas vezes está associada a hipertensão intracraniana, vasculite e alterações eletrolíticas.…”
Section: Variáveisunclassified
“…The CSF cell count and the cryptococcal antigen titers of CSF and serum did not normalize either. It was reported that serum and CSF titers of >1:8 at one month or more after treatment in patients with cryptococcosis are associated with relapse (18). However, two weeks after bilateral adrenalectomy, the CSF cell count decreased to the normal range and the CSF and serum cryptococcal antigen titers became negative in the present patient.…”
Section: Discussionmentioning
confidence: 45%
“…However, the survivors showed a good response to antifungal therapy (1,3). Intravenous amphotericin B with or without flueytosine, is usually the standard form of therapy (18). Recently, an increasing number of reports have been published concerning AIDS-associated cryptococcal meningitis (9)(10)(11)(12)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…4 weeks). 22 However, with the advent of HIV infection and its severe immunosuppression, a new strategy was adopted, which included induction, clearance and suppression phases of treatment. In the initial induction phase, it was found that the combination of amphotericin B plus flucytosine reproducibly reduced CSF yeast counts over 2 weeks of treatment and also reduced the numbers of relapse cases.…”
Section: Challenge Recommendationmentioning
confidence: 99%